Cross-theoretical explorations of interlocutors and their individual differences - Gurzynski-Weiss, Laura (Language learning and language teaching ;, 2020)
"Cross-theoretical Examinations of Interlocutors and their Individual Differences examines interlocutors and their individual differences from four theoretical lenses: the cognitive-interactionist approach, sociocultural theory, the variationist approach, and complexity theory. Each section explores what role(s) these individuals have, assesses how their theorized IDs influence L2 learning opportunities and processes, and provides empirical examples of how such research may be robustly undertaken within each framework. The concluding chapter synthesizes the theoretical overviews and empirical studies, highlighting connections across approaches and outlining robust steps for future research. Collectively, the chapters in this edited volume provide an opportunity to address the relationship(s) between interaction among interlocutors (however theorized), and to shed light on how these individuals have the potential to impact the central concern of second language acquisition, L2 development. To maximize readability and impact, the chapters follow the same organizing questions, inviting the engagement of L2 researchers, students, and teachers alike"--